2023
DOI: 10.3389/fspas.2022.1109086
|View full text |Cite
|
Sign up to set email alerts
|

Testing parity symmetry of gravity with gravitational waves

Abstract: The examination of parity symmetry in gravitational interactions has drawn increasing attention. Although Einstein’s General Relativity is parity-conserved, numerous theories of parity-violating (PV) gravity in different frameworks have recently been proposed for different motivations. In this review, we briefly summarize the recent progress of these theories, and focus on the observable effects of PV terms in the gravitational waves (GWs), which are mainly reflected in the difference between the left-hand and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Current and future GW observations can constrain these gravitational theories with high accuracy [43][44][45][46][47][48][49][50][51][52]. Some kinds of modified theories, including parity-violating effects, have been studied in recent years [53][54][55][56][57][58][59][60][61][62][63][64][65][66], like Chern-Simons (CS) gravity [26,67] (consisting of dynamical and non-dynamical cases), ghost-free parity-violating theory [68][69][70][71][72], Nieh-Yan modified teleparallel gravity [73,74], parity-violating symmetric teleparallel gravities [75] and the general spatial covariant gravities [31,32,60,61,63,[76][77][78]]. As a typical example, CS theory introduces a coupling term between the pseudo-scalar and Pontryagin density in the Einstein-Hilbert action, which causes the nonconservation of the CS topological current.…”
Section: Jcap04(2023)006 1 Introductionmentioning
confidence: 99%
“…Current and future GW observations can constrain these gravitational theories with high accuracy [43][44][45][46][47][48][49][50][51][52]. Some kinds of modified theories, including parity-violating effects, have been studied in recent years [53][54][55][56][57][58][59][60][61][62][63][64][65][66], like Chern-Simons (CS) gravity [26,67] (consisting of dynamical and non-dynamical cases), ghost-free parity-violating theory [68][69][70][71][72], Nieh-Yan modified teleparallel gravity [73,74], parity-violating symmetric teleparallel gravities [75] and the general spatial covariant gravities [31,32,60,61,63,[76][77][78]]. As a typical example, CS theory introduces a coupling term between the pseudo-scalar and Pontryagin density in the Einstein-Hilbert action, which causes the nonconservation of the CS topological current.…”
Section: Jcap04(2023)006 1 Introductionmentioning
confidence: 99%
“…Cosmological models, such as those described in refs. [57][58][59][60][61], can generate chirality through parity-violating interactions. A finite sum of nearby SMBHBs can also produce a random fraction of chirality [62][63][64].…”
Section: Power-law Stochastic Gravitational Wave Backgroundmentioning
confidence: 99%
“…Other recent studies on parity violating gravities can be found in Refs. [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%